Bionomia e comportamento de nidificação da abelha Epanthidium tigrinum (hymenoptera – megachilidae) em ninhos- armadilha - Gomes, Angela Maria da Silva (2016)
Many species of solitary bees have potential to be used in agriculture as pollinators, such as the Megachilidae Family bees, used in pear, apple, almonds, alfalfa, among other crops. In Brazil, this family is represented by the subfamily Megachilinae, composed of five taxos, one of which is the Anthidini tribe. This study aimed to describe the bionomics and life cycle of the Epanthidium tigrinum bee (SCHROTTKY, 1905) and to identify the floral types visited by these species. Trap nests made of black paper placed on wooden blocks were used and installed on places covered to protect them against environmental changes. Daily observations were made to accompany the foundation of the nests until their closing. Five bees were labeled with non-toxic paint when they initiated the nest building, and these were observed for a period of five days to monitor the nesting behavior. Completed nests were kept in B.O.D. until the emergence of adult bees, being sectioned to monitor the sex ratio. The residual material of the postemergence cells was collected for analysis andcrop palynological identification of the diet of individuals. A couple of bees of each nest was sacrificed in ethyl acetate, assembled and sent for identification by experts. The studied bees showed no seasonality, but there was a negative correlation with temperature for number of nests (rs = - 0,639; p = 0.034) and number of cells (rs = -0,702; p = 0.016). In the nests, there was the emergency of 67 bees, 37 males and 30 females, resulting in a sex ratio of 1.2: 1 and a mortality rate of 18.5%. The bees have built an average of 1.6 nests with the average number of cells of 5.06 ± 2.32, with average size of 7,97mm ± 1,31mm, and 15.44 ± 5.93 days to complete the nest. The young took an average of 43.69 ± 4.64 of emergency. Females began to forage as 7: 50 h ± 30 min a.m. and remained active until 4 p.m. The bees were kept inside the nest on average of 9 ± 7min and in field for 19 ± 5 minutes.In the morning hours these bees collected pollen and in the afternoon they produced resin, and the greater flow in the nests occurred during 2p.m. The availability of resin was a limiting factor for the construction of nests. The analysis showed 27 croppalynological constituent species from their diet, and the pollen Byrsonima crassifolia and Vigna sinensis were the most important, with 68.39% and 15.36% of the total, respectively.